Efektivitas Lembar Kerja Siswa dengan Model Project Based Learning Pada Materi Bangun Ruang Sisi Datar Siswa Kelas VIII SMP - Sri ulfa Insani (Departement of Mathematics Education, 2022)
The aim of this research is to produce Student’s Worksheet based on project-based learning model with has good validity, practicality, and effectiveness, for Geometry Solids lesson at students of class VIII SMP Negeri 18 Pekanbaru. This is development research by applying the ADDIE model procedure. The research subjects were 32 students in class VIII 8. The techniques data collection used were test and non-test techniques. The research instruments were validation sheets, practicality sheets, and learning achievement questions. The results showed that the Mathematics Student’s Worksheet with the Project Based Learning Model was included in the very valid category with an average score = 4.53, included in the very practical category with an average score = 4.12, and included in the effective category based on the calculation of the value and , which means that the proportion of students who have achieved KKM is more than 74.99%.